Degeneration of spinal ganglion and segmental apparatus of the spinal neurons in sciatic nerve injury: an experimental study - Vladimir S. Tolkachev; Sergey P. Bazhanov; Olga V. Matveeva; Galina A. Korshunova; Stanislav D. Shuvalov; Valdimir Yu. Ulyanov; Vladimir V. Ostrovskij (Russian Open Medical Journal)
Objective — To investigate the extent of degenerative changes in neurons of spinal ganglion and segmental apparatus in various injuries to sciatic nerve in the experiment on white rats. Material and Methods — The research involved 40 white non-pedigree male rats distributed among four groups. The animals of Group 1 (n=10) underwent the compression of nerve trunks with Mosquito clamp forceps for 15 minutes. In Group 2 (n=10), the animals had their nerve trunks ligated; and in Group 3, they had their nerves completely transected in their middle thirds. The separate group of control animals (n=10) suffered no damage to their sciatic nerves. Spinal cords and spinal ganglia at L4-L6 level were the material for histopathological examination. We calculated the number (percent) of degenerated neurons in spinal cords and spinal ganglia at the affected sides on Day 30, and compared them to those at the intact sides. Results — The number (percent) of degenerated neurons in spinal cord and spinal ganglion, expressed as Me (Q1; Q2), constituted 2.52% (1.92; 2.74) and 3.75% (2.37; 4.74) in Group 1, 9.27% (9.03; 9.94) and 16.74% (16.01; 18.22) in Group 2, 25.59% (24.36; 26.29) and 31.94% (31.44; 33.03) in Group 3, respectively. Depending on the number (percent) of degenerated neurons, we classified three grades of change manifestation: mild (Group 1), medium (Group 2), and severe (Group 3). No degenerated neurons were found in the control animals. Conclusion — The compression, ischemic exposure on the sciatic nerve, and complete anatomical transection of its trunk resulted in Wallerian degeneration, as well as degeneration of segmental apparatus in spinal cord neurons.